2016
DOI: 10.3389/fenrg.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

Improving NASICON Sinterability through Crystallization under High-Frequency Electrical Fields

Abstract: The effect of high-frequency (HF) electric fields on the crystallization and sintering rates of a lithium aluminum germanium phosphate (LAGP) ion conducting ceramic was investigated. LAGP with the nominal composition Li1.5Al0.5Ge1.5(PO4)3 was crystallized and sintered, both conventionally and under effect of electrical field. Electrical field application, of 300 V/cm at 1 MHz, produced up to a 40% improvement in sintering rate of LAGP that was crystallized and sintered under the HF field. Heat sink effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Among the numerous types of solid lithium-ion conductorsLISICONs, NASICONs, garnets, (anti-)­perovskites, and sulfide-based systems NASICON materials are widely investigated. Na Super Ionic CONductor (NASICON) describes a family of ionic conductors with the structure of NaZr 2 (PO 4 ) 3 , which crystallizes in the R 3̅ c space group (International tables #167). , Apart from different sodium-containing compounds, there exist also stable lithium-ion conductors within this structure type. The general formula of lithium-conducting NASICON materials is based on Li M (PO 4 ) 3 with M being a tetravalent metal ion. The basic structure consists of LiO 6 units in a trigonal antiprismatic coordination, M O 6 octahedra, and PO 4 tetrahedra.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous types of solid lithium-ion conductorsLISICONs, NASICONs, garnets, (anti-)­perovskites, and sulfide-based systems NASICON materials are widely investigated. Na Super Ionic CONductor (NASICON) describes a family of ionic conductors with the structure of NaZr 2 (PO 4 ) 3 , which crystallizes in the R 3̅ c space group (International tables #167). , Apart from different sodium-containing compounds, there exist also stable lithium-ion conductors within this structure type. The general formula of lithium-conducting NASICON materials is based on Li M (PO 4 ) 3 with M being a tetravalent metal ion. The basic structure consists of LiO 6 units in a trigonal antiprismatic coordination, M O 6 octahedra, and PO 4 tetrahedra.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have already been carried out to develop a suitable RT solid electrolyte material. [13][14][15][16] In this regard nonoxide chalcogenide glasses (Na 2 (Ga 0.1 Ge 0.9 ) 2 14 In general, NASICON and the relevant solid electrolytes are produced using a conventional solid state reaction process, which includes sintering and calcination over 1100 C. 22 The sintering process usually leads to the formation of voids and may disturb the development of new structured materials to gain high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“… 14 In general, NASICON and the relevant solid electrolytes are produced using a conventional solid state reaction process, which includes sintering and calcination over 1100 °C. 22 The sintering process usually leads to the formation of voids and may disturb the development of new structured materials to gain high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently Yu et al reported the reduction in furnace temperature for sintering of ceramics as a function of AC frequency. From a limited number of such studies it appears that AC fields have a similar effect on sintering rate of ceramic green bodies as DC flash sintering . A review of the current state of flash sintering compares the current density and volumetric power density of various test conditions and ceramics samples .…”
Section: Introductionmentioning
confidence: 99%
“…From a limited number of such studies it appears that AC fields have a similar effect on sintering rate of ceramic green bodies as DC flash sintering. 6,7 A review of the current state of flash sintering compares the current density and volumetric power density of various test conditions and ceramics samples. 5 Here, the power density between both DC and AC tests is similar, ranging from 10 to 100 mW/mm 2 .…”
Section: Introductionmentioning
confidence: 99%